2020
DOI: 10.3991/ijet.v15i17.16735
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation Model for the Cultivation and Improvement of the Innovation Ability of College Students

Abstract: In modern times, the innovation ability of college students is a focus of college education. However, the cultivation and improvement of this ability are constrained by many factors, and the ability is too complex to be evaluated accurately. To solve the problems, this paper puts forward an extension model suitable for evaluating the cultivation and improvement of the said ability. Firstly, the research problem was defined clearly as the evaluation of the cultivation and improvement for the innovation ability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…According to the actual case study, the current sports professional academics and teachers in the scientific research and innovation ability are the shortcomings, and they indicate the direction to promote the teachers and students of sports academic research and innovation ability to improve. Literature [14] designed a framework for judging the level and development of students' innovation ability, and empirical analysis methods were used to corroborate the feasibility of the proposed assessment framework. Literature [15] designed an analytical framework based on grey system theory and hierarchical Analysis to understand the logic of the teacher-student collocation teaching model to develop students' knowledge innovation ability and gave some constructive optimization solutions to provide some ideas for the development of students' knowledge innovation ability.…”
Section: Introductionmentioning
confidence: 99%
“…According to the actual case study, the current sports professional academics and teachers in the scientific research and innovation ability are the shortcomings, and they indicate the direction to promote the teachers and students of sports academic research and innovation ability to improve. Literature [14] designed a framework for judging the level and development of students' innovation ability, and empirical analysis methods were used to corroborate the feasibility of the proposed assessment framework. Literature [15] designed an analytical framework based on grey system theory and hierarchical Analysis to understand the logic of the teacher-student collocation teaching model to develop students' knowledge innovation ability and gave some constructive optimization solutions to provide some ideas for the development of students' knowledge innovation ability.…”
Section: Introductionmentioning
confidence: 99%
“…In order to provide guidance to learners in making learning decisions, a necessary work is to thoroughly analyze and research the changing laws of learners' learning behavior [1][2][3][4][5][6][7][8][9]. This research involves professional knowledge of psychology, pedagogy, sociology, and other disciplines, through descriptive statistics on the learning behavior of different groups, it can be found that individuals in learning groups have a few similarities in terms of the regularity of learning time, requirement for learning resources, and requirement for tutoring and accompanying [10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…e specific steps of the algorithm were given. Wang and Yan [30] proposed an extension model for evaluating students' ability cultivation and improvement: the problem was clearly defined as the evaluation of the cultivation and improvement of college students' innovation ability, an evaluation model was established to train and enhance that ability, the workflow of the model was explained, and the evaluation algorithm was designed in detail.…”
Section: Introductionmentioning
confidence: 99%